Windows 98 : No Experience Required - Crawford, Sharon (New Delhi BPB Publications, 1998)
This guide to Windows 98 uses pictures and over 800 screenshots rather than lengthy explanations. The book is aimed at the vast majority of new users who need to learn the most useful features quickly. It covers all the new features including the Active Desktop.
Include Picture
Keywords: Operating systems (Computers) -- Microsoft Windows (Computer file)